Antimicrobial properties and immune-related gene expression of a C-type lectin isolated from Pinctada fucata martensii. Issue 105 (October 2020) - He, Junjun; Shen, Chenghao; Liang, Haiying; Fang, Xiaochen; Lu, Jinzhao
Abstract: C-type lectins are carbohydrate-binding proteins that play important roles in the innate immune response to pathogen infections. Here, multi-step high performance liquid chromatography (HPLC), combined with mass spectrometry (MS), was used to isolate and identify proteins with antibacterial activity from the serum of Pinctada fucata martensii . Using this method, we obtained a novel isoform of C-type lectin (PmCTL-1). PmCTL-1 strongly inhibited gram-positive bacteria. The complete cDNA sequence of PmCTL-1 was 636 bp in length, and encoded a protein 149 amino acids long, containing a typical carbohydrate recognition domain (CRD). A phylogenetic analysis based on a multiple sequence alignment indicated that PmCTL-1 was highly similar to C-type lectins from other mollusks. Fluorescent quantitative real-time PCR analysis showed that PmCTL- 1 mRNA was strongly upregulated in the mantle of healthy P.f. martensii, but was expressed only at low levels in the gill, gonad, hepatopancreas, adductor muscle, and hemocytes. PmCTL-1 expression levels in the mantle and hemocytes increased significantly in response to bacterial stimulation. This study provides a valuable framework for further explorations of innate immunity and the immune response in mollusks. Highlights: A novel C-type lectin (PmCTL-1) was identified from Pinctada fucata martensii. The cDNA sequence of PmCTL-1 was characterized by RACE method. PmCTL-1 showed antimicrobial activities against Gram-positive bacteria. The mantle is the main tissue for PmCTL-1 expression. The expression level of PmCTL- 1 mRNA transcripts was significantly up-regulated after bacteria induction.